Reflection Model Strategy as a Source of Ideas in Writing Short Stories (Case Study on High School Students) - Marwani; Ribut Wahyu Eriyanti; Hari Sunaryo (Mimbar Ilmu, 2025)
This study aims to explore the implementation of a reflective model in short story writing instruction at the senior high school level and to examine its impact on students’ writing quality. Short story writing, as a fundamental skill in Indonesian language learning, is expected to foster students’ creativity, enhance critical thinking skills, and strengthen idea development in writing. However, previous studies indicate that many senior high school students still experience difficulties in producing high-quality short stories. One instructional approach that has the potential to improve students’ writing quality is the use of a reflective model, which allows students to evaluate the strengths and weaknesses of their work and to plan revisions for subsequent drafts. This study employed a qualitative approach using a case study method in a senior high school, involving 40 students from grade XI or XII. Data were collected through classroom observations, interviews, analysis of students’ short stories, and reflective journals. The findings reveal that the implementation of the reflective model contributed to improvements in the quality of students’ short stories, particularly in terms of idea development, plot organization, character development, and language use. Reflection helped students think more critically about their writing, address structural weaknesses in their narratives, and develop more vivid and coherent characters. Although challenges related to time constraints and students’ understanding of reflection were identified, the study concludes that reflective practices are effective in enhancing students’ writing skills and have the potential to be more widely implemented in short story writing instruction at the senior high school level.